Where are the world's fastest Ironman® 70.3 race courses for professional athletes? - Thuany, M.; Valero, D.; Villiger, E.; Andrade, M.; Weiss, K.; Nikolaidis, P.; Cuk, I.; Knechtle, B. (Journal of Science and Cycling, 2023)
The dominance of certain nations in certain sports disciplines is well knowed in scientific context. For triathlon, it has been reported that most of the finishers, and the fastest in Ironman® Hawaii originated from the United States of America. However, nothing is known regarding the role of specific race courses in athletes' performance. The present study aimed to analyze where the fastest split and overall race times for Ironman® 70.3 races were achieved. The locations of the fastest Ironman® 70.3 competitions were processed throughout 163 different event locations. Race records were aggregated by location, and the split and full finish times. The Ironman® 70.3 races in Dubai, Kronborg, and Mandurah presented the fastest race course. For split disciplines, the fastest swim times were recorded for women and men in the Ironman® 70.3 races in Busan, Panama, and Augusta. For cycling, the fastest times were achieved for both women and men in Ironman® 70.3 Tallinn, followed by the Ironman® 70.3 Dubai and Bahrain. The fastest running times were recorded for women and men in Ironman® 70.3 Kronborg, the Ironman® 70.3 Nice, and Les Sables d`Olonne. Differences among the race course were found, except for the running discipline. Professional triathletes and coaches could use this information to design optimal race courses and training strategies for performance improvement.